Savings and loan business: its purpose, functions, and economic justification - Kendall, Leon T. (Englewood Cliffs, 1962)
The savings and loan business welcomes continued investigation by sincere researchers and scholars into its role in the American financial community. Although the contents of this monograph represent a rea soned analysis of our purposes and functions in light of today's knowl edge, we realize full well that the future will bring further refinement in these premises and more appropriate interpretation and explanation of our role in the light of greater knowledge. A note on terminology is appropriate. In this monograph, savings and loan associations will be referred to from time to time simply as savings associations. The phrase "savings account will be in common usage, but the term "share account" will be conspicuous by its absence.
Keywords: Financial economics